2002
DOI: 10.1074/jbc.m200887200
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Amyloid-β1–42, but Not Extracellular Soluble Amyloid-β Peptides, Induces Neuronal Apoptosis

Abstract: Alzheimer disease (AD), the most frequent cause of dementia, is characterized by an important neuronal loss. A typical histological hallmark of AD is the extracellular deposition of ␤-amyloid peptide (A␤), which is produced by the cleavage of the amyloid precursor protein (APP). Most of the gene mutations that segregate with the inherited forms of AD result in increasing the ratio of A␤42/A␤40 production. A␤42 also accumulates in neurons of AD patients. Altogether, these data strongly suggest that the neuronal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
138
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 185 publications
(152 citation statements)
references
References 47 publications
14
138
0
Order By: Relevance
“…Although these triple transgenes had large extracellular deposits of A␤ peptides in their brains as the disease progressed, which were similar in appearance to the plaques seen in human AD, most of the immunologically detectable A␤ was first seen inside neurons, not in the extracellular spaces. These findings confirm what many previous investigators have noted, that the initial manifestations of A␤ accumulation begin inside neurons, with the earliest detectable material located inside membranous compartments, which some have identified as endosomal or lysosomal (4)(5)(6). Although this latest triple transgene satisfies the criticisms directed to earlier transgene models that lacked one or more features of the human disease, we should remember that no patient has yet been described who has, as far as we know, a comparable genetic burden.…”
supporting
confidence: 80%
“…Although these triple transgenes had large extracellular deposits of A␤ peptides in their brains as the disease progressed, which were similar in appearance to the plaques seen in human AD, most of the immunologically detectable A␤ was first seen inside neurons, not in the extracellular spaces. These findings confirm what many previous investigators have noted, that the initial manifestations of A␤ accumulation begin inside neurons, with the earliest detectable material located inside membranous compartments, which some have identified as endosomal or lysosomal (4)(5)(6). Although this latest triple transgene satisfies the criticisms directed to earlier transgene models that lacked one or more features of the human disease, we should remember that no patient has yet been described who has, as far as we know, a comparable genetic burden.…”
supporting
confidence: 80%
“…3A) (47)(48)(49)(50). Oligomeric A␤-(1-42) significantly reduced neuronal viability compared with fibrillar species at 0.01, 0.1 and 1.0 M. Unaggregated peptide had significantly less effect on neuronal viability than fibrillar or oligomeric A␤, exhibiting a biphasic response of neurotrophic effects at low concentrations (1-100 nM) and neurotoxic effects at higher concentrations (1-15 M).…”
Section: Resultsmentioning
confidence: 96%
“…In addition to APP, we also examined intracellular Aβ as increasing evidence suggests that intracellular Aβ accumulation precedes plaque and neurofibrillary tangle formation and is an early event in the disease process (Wilson et al, 1999;Gouras et al, 2000;Gouras et al, 2005). Kienlen-Campard et al (2002)have shown that long term expression of human APP in rat cortical neurons induce neuronal apoptosis that is dependent on intracellular but not extracellular Aβ. In this study, no differences in intracellular Aβ expression in lymphocytes or monocytes were found.…”
Section: Discussionmentioning
confidence: 99%